IMPLEMENTATION OF LAW AUTHORITY AND RESPONSIBILITY OF BUDGET USERS IN PROCUREMENT OF GOODS AND SERVICES IN HEALTH - Taty Sugiarti Ramlan; Dewi Kania Sugiarti (Jurnal Dinamika Hukum, 2017)
The opening (preambule) of 1945 Constitution in paragraph IV has a goal to make a public welfare based on social justice in all fields including health. Government as a state administrator is obliged to provide all public needs in terms of goods, services, and or infrastructure development including health. The procurement of goods and services by Government is an arranged method and procedure to acommodate government activities in health care. The Budget Users (BU) is a responsible official on allocating the budget of goods/services procurement. Practically speaking, BU is often confronted by  criminal accountability toward the BU personally rathertha by administrative law toward the BU over his position. In fact, BU is not only governed by behavioral norms (gedragsnorm) but also position norms (bestuursnorm).Keywords: public procurement, budget Users, law responsibility